Analisis Konflik Internal dan Model Penyelesaian Konflik Internal Antar Anggota dan Pengurus Serikat Pekerja pada PT. Fumira Semarang - Nur Anif Fulasifah; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2017)
between member or between member with organizing committee of the company. Internal conflict thta happen within organization will be very influential with the development and the process of every aspect of the event in organization, due there are negative and positive impacts that caused by this internal conflict. Furthermore, company must have a conflict resolution model that very accurate so it can provide a solution as a whole as well as effective and efficient. Alleged factors that cause internal conflict are the differences in opinions, views, desires, and the goals among members of the organization causing dissatisfaction with the leader of the organization due it is considered not able to resolve the conflict well.The purpose of the research is to analyze internal conflict that happened in PT. FUMIRA’s SPSI which is between members and leader of SPSI along the cause and conflict resolve model which is conducted by SPSI.This research is using accumulation with in depth interview with the research subject. This research shows that internal conflict within SPSI is caused by differences of interest between SPSI member concerning the number of Labor Union in PT. FUMIRA SEMARANG, where as part of the member want to establish new labor union and the other part of the member want to continue as one union labor, as they want to hasten change of the leader. Due lack of sattisfaction of the member with the SPSI leader’s performance. This conflict can be solved with using Bipatrit conflict resolution model, where this conflict not only causing negative impact to the product quality but also causing positive impact in evaluation of the system and development of the worker’s competencies for SPSI and PT. FUMIRA in general.This research suggest that there must be a trust between SPSI’s leader and also the member so it can minimize the disputes on SPSI in the future.